The translation of Fernando Iwasaki's "Ajuar funerario": A case study of two fantastic short-short stories of terror - Lambrechts, Ellen (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
Abstract: According to Andres-Suárez, we live in the «era of brevity». As far as literature is concerned, we observe that the shorter stories are, the more significance their words gain. Indeed, the volume Ajuar funarario (2004), written by the Peruvian author Fernando Iwasaki (Lima, °1961), contains eighty-nine short-short stories and almost all of them have a fantastic meaning which the reader is unable to discern with certainty and which, therefore, strikes terror into him. The present article undertakes the analysis of «El dominio» and «No hay que hablar con extraños», two short-short stories which open up a fantastic dimension that renews the traditions of the genre by focusing not only on thematic elements, but also, and above all, on the way these are introduced in the narration. As we compare the stories with their English versions, we find that the translations conform to the norms of the target literary system, disambiguating the narrative enunciations and, consequently, taking away the fantastic and the terror from them.
Keywords: Fantastic narrative; terror; translation; Fernando Iwasaki